Magnito-mineralogicheskie i biologicheskie pokazateli donnykh otlozhenii oz. Bol’shoi Khabrei (Magneto-Mineralogical and Biological Properties of Sediments of the Lake Bolshoy Kharbey) - Nazarova, L.; Frolova, L.; Kosareva, L.; Rudaya, N.; Syrykh, L.; Gafiatullina, L.; Kuzina, D.; Palagushkina, O.; Tumanov, O.; Fefilova, E.; Loskutova, O. (2014)
Investigation of sediment cores from the lake Bolshoy Kharbey (Bolshezemelskaya tundra) was performed using magnetic-mineralogical and palaeobiological methods, including palynological, Cladocera and chironomid analysis. It was shown that noticeable changes took place in the state of sediments and communities of hydrobionts. Lower part of the sediments is characterized by lower ferromagnetic component, which is related to lower number of magnetotactic bacteria, producing biologically controlled magnetic minerals. Upper part of the core is characterized by higher values of magnetic susceptibility and its components. Pollen analysis has shown that vegetation of the region during the time of the investigated sedimentation was dominated by conifers and by constant presence of dwarf birch, Alnus fruticosa, Ericaceae. Herbaceous are represented mainly by sedge, reflecting local near-water vegetation. Larch pollen disappears gradually from the lake sediments, alongside with the increase of the concentrations of birch and Alnus fruticosa pollen. Taxa characteristic for big water bodies, mainly from the family Bosminidae, dominate Cladoceran communities. The most frequent zooplanktonic taxa in the whole core were Chydorus. cf. sphaericus, Eubosmina cf. longispina, small forms of the genera Alona. Chironomid communities are represented mainly by acid-tolerant, temperate, littoral-sublittoral taxa. In the upper layers of sediments in cladoceran and chironomid communities share of planktonic taxa increases which indicates rise of the lake level as a result of seasonal ground melting. At the same time gradual succession in the local vegetation starts. Concentrations of the birch and larch pollen decrease, and Pinus s/g Diploxylon increase. This can indicate that climate became warmer and drier. Communities of hydrobionts are getting more diverse, the number of the acidophilic, phytophylic taxa and taxa, characteristic for eutrophication grows. In palynospectra concentration of ferns and sphagnum grows, which can indicate ...